Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1242/dev.175950
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein DND1 acts sequentially as a negative regulator of pluripotency and a positive regulator of epigenetic modifiers required for germ cell reprogramming

Abstract: The adult spermatogonial stem cell population arises from pluripotent primordial germ cells (PGCs) that enter the fetal testis around embryonic day (E)10.5. PGCs undergo rapid mitotic proliferation, then enter prolonged cell cycle arrest (G1/G0), during which they transition to pro-spermatogonia. In mice homozygous for the Ter mutation in the RNA-binding protein Dnd1 (Dnd1 Ter/Ter), many male germ cells (MGCs) fail to enter G1/G0 and instead form teratomas: tumors containing many embryonic cell types. To inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 60 publications
6
32
0
Order By: Relevance
“…DND1 deletion causes loss of PGCs by reactivation of somatic gene expression patterns in zebrafish (Gross-Thebing et al 2017;Weidinger et al 2003). In mice, truncations of DND1 (the so-called 'Ter-mutation') lead to male sterility and the formation of testicular teratomas (Ruthig et al 2019;Youngren et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DND1 deletion causes loss of PGCs by reactivation of somatic gene expression patterns in zebrafish (Gross-Thebing et al 2017;Weidinger et al 2003). In mice, truncations of DND1 (the so-called 'Ter-mutation') lead to male sterility and the formation of testicular teratomas (Ruthig et al 2019;Youngren et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Photoactivatable-ribonucleoside-enhanced crosslinking and immunoprecipitation (PAR-CLIP) assays revealed that targets crosslinked to DND1 are enriched in a UUU/UUA triplet and are associated with apoptosis, inflammation and signaling pathways (Yamaji et al 2017). An additional digestion optimized-RIP-seq (DO-RIP-seq) approach described [A/G/U]AU[C/G/U]A[A/U] as RNA sequence motif enriched in DND1 targets (Ruthig et al 2019). Transcriptome sequencing of the Ter mouse line, possessing a truncation in the DND1 gene, just before the formation of teratomas, showed two groups of DND1 targets either down-or up-regulated, involved in pluripotency and in differentiation respectively, in a sequential fashion, suggesting a dual and biphasic role for DND1.…”
Section: Introductionmentioning
confidence: 99%
“…DND1 interacts with specific mRNAs as well as proteins to function as a translational regulator to up-regulate or down-regulate translation from mRNAs (Aguero et al, 2018;Kedde et al, 2007;Suzuki et al, 2016;Yamaji et al, 2017). The mRNA targets of DND1 have been identified to include cell cycle regulators, apoptotic factors, DNA repair proteins and pluripotency factors (Cook, Munger, Nadeau, & Capel, 2011;Kedde et al, 2007;Ruthig et al, 2019;Yamaji et al, 2017;Zhu, Iacovino, Mahen, Kyba, & Matin, 2011). DND1 regulates translation from mRNAs through different mechanisms including by blocking miRNA function (Gu et al, 2018;Kedde et al, 2007), cooperating with CCR4-NOT complex (Suzuki et al, 2016;Yamaji et al, 2017) and other proteins (Aguero et al, 2017;Suzuki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…DND1 regulates translation from mRNAs through different mechanisms including by blocking miRNA function (Gu et al, 2018;Kedde et al, 2007), cooperating with CCR4-NOT complex (Suzuki et al, 2016;Yamaji et al, 2017) and other proteins (Aguero et al, 2017;Suzuki et al, 2016). DND1-mediated translational regulation helps maintain localized expression of critical proteins in germ cells and in early embryos (Mei et al, 2013;Mishima et al, 2006) and modulates cell proliferation, pluripotency and reprogramming of germ cells to maintain germ cell fate (Cook et al, 2011;Gross-Thebing et al, 2017;Ruthig et al, 2019;Suzuki et al, 2016;Yamaji et al, 2017). The ability of DND1 to function as translational regulator has also been experimentally demonstrated in cancer cells such as in breast cancer cell lines, acute myeloid leukemia cells, and others (Bhandari et al, 2013;Cheng et al, 2017;Liu et al, 2010;Wampfler et al, 2016) where translational upregulation by wildtype DND1 facilitated differentiation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation